The hybrid nanosystem for the identification and magnetic hyperthermia immunotherapy of metastatic sentinel lymph nodes as a multifunctional theranostic agent - Qin, Qiaoxi; Zhang, Qin; Li, Pan; Wang, Ronghui; Liu, Ying; Deng, Ruxi; Zhang, Juanmin; Nie, Quanyu; Zhou, Hong; Zhou, Yang (Frontiers in Bioengineering and Biotechnology, 2024)
Lymphatic metastasis is the main cause of early-stage tumor spread, making the identification and therapy of metastatic sentinel lymph nodes (SLNs) are highly desirable in clinic. Currently, suspected malignant SLNs typically undergo a series of independent operations in clinical practice, including imaging, staining, sentinel lymph node biopsy (SLNB) and lymph node dissection (LND), which brings inconvenience to diagnosis and treatment, and may cause postoperative complications for patients.Moreover, the ordinary removal of tumor-draining lymph nodes (TDLNs) may do harm to systemic immunity required for tumor eradication. Hence, we utilized the hybrid nanosystem (SPIOs+RPPs) we constructed before for the integrated staining, ultrasound imaging, and therapy of metastatic SLNs. In this study, SPIOs+RPPs could migrate into SLNs successfully to stain them black for easy visual identification.Beyond staining, the hybrid nanosystem could realize contrast enhanced ultrasound (CEUS) imaging in SLNs. Meanwhile, it could inhibit cancer cells to lower the tumor burden and reverse immune-suppressive microenvironment of metastatic SLNs effectively via magnetic hyperthermia immunotherapy in VX2 tumor-bearing rabbits with popliteal fossa lymph node metastasis. These findings indicate that SPIOs+RPPs is a potential multifunctional theranostic agent for detection and therapy of lymphatic metastasis.